Secondary breast reconstruction after mastectomy using the DIEP flap - Hauck, Theresa; Horch, Raymund E.; Schmitz, Marweh; Arkudas, Andreas (Surgical Oncology-Oxford, 2018)
INTRODUCTION: Breast reconstruction is an important element in the successful therapy of breast cancer [1]. Thereby, autologous microvascular breast reconstruction has been shown to be a reliable technique. The use of a deep inferior epigastric perforator (DIEP) flap or a muscle-sparing (MS) free transverse rectus abdominis musculocutaneous (TRAM) flap is recognized in many centres as gold standard for reconstructive options [2-4]. Based on our experiences with 137 patients over a 5-year period we want to highlight the technical aspects of the free microsurgical autologous breast reconstruction using a DIEP flap. PATIENTS AND METHODS: Between 01/2013 and 12/2017 we treated 137 patients (age 32-78 years, mean age 52 years) after mastectomy with autologous microsurgical free flap breast reconstruction. A DIEP flap was used for breast reconstruction in 33 patients. In 104 cases, we performed a muscle sparing TRAM flap. In this video we demonstrate the typical sequence of operative steps of a DIEP flap in a 32 year old patient after mastectomy due to an invasive ductal breast carcinoma. RESULTS: The rate of total flap loss in our department was 2.2% including all patients. In less than 1%, partial flap necrosis could be observed. 61% of the patients had undergone previous irradiation. Within the small number of flap loss, we could not observe a trend towards a correlation between flap loss and previous irradiation. CONCLUSION: Autologous breast reconstruction using a DIEP or MS-TRAM flap provides a surgically safe technique including a low incidence of flap loss in specialized centres.
EVALuna2:211470